A mechanism of regucalcin knock-down in the promotion of proliferation and movement of human cervical cancer HeLa cells - Li, Xiaolong; Huang, Yingwen; Wang, Pengfei; Song, Wei; Yao, Qingmei; Hu, Qiping; Zhou, Sufang (Translational Cancer Research, 2019)
Background: Regucalcin (RGN) has been reported to have inhibitory effects on the proliferation and migration of many cancer cells. In this research, RGN expression has been silenced to study its effects on human cervical cancer HeLa cells. Methods: Lentivirus mediated siRNA was infected into HeLa cells by lentivirus vector. The RGN expression was measured by quantitative real-time PCR (RT-qPCR) and Western blotting (WB). Cell count kit-8, colony formation assay and transwell assay were used to detect cell proliferation, migration and invasion. The expression of Wnt/β-catenin pathway and epithelial-mesenchymal transition (EMT) related proteins, including β-catenin, GSK-3β, p-GSK-3β, matrix metalloproteinase-3 (MMP-3), matrix metalloproteinase-7 (MMP-7), matrix metalloproteinase-9 (MMP-9), E-cadherin, N-cadherin and vimentin, were detected by WB. Results: Compared with HeLa-NC cell line, the expressions of RGN and E-cadherin in HeLa-siRGN cell lines are significantly decreased, while the expressions of β-catenin, MMP-3, MMP-7, MMP-9, p-GSK-3β, N-cadherin and vimentin increased. The RGN down-regulation has been observed to promote cell proliferation, enhanced cell migration and invasion. Conclusions: The down-regulation of RGN may enhance the activity of metastasis related signaling pathway Wnt/β-catenin and EMT in the progression of cervical cancer.